Self-reported competency, knowledge and practices of teachers teaching primary children with autism in government schools of West Malaysia: a cross-sectional study - Galvan, Jo Ann Andoy; Shridhar Patil, Sapna; Nair Ramalingam, Prabhagari; Shobri, Muhammad Aminul Syahmi; Chinna, Karuthan; Sahrir, Muhammad Sabri; Chidambaram, Kumarappan (F1000Research, 2020)
Background: Disability brings challenges and demands in the family and society which last for a long time. Children that are affected by disability are often kept at home, without access to opportunities other children might have, and education is one of the most effective ways to break the cycle of discrimination and poverty. Malaysia is committed to achieving the Sustainable Development Goals, and teacher quality issues are among the Ministry of Education's focuses to ensure a successful journey for pupils with disabilities. In this study, we evaluated the competency, knowledge and implementation practices of teachers serving government schools in West Malaysia regarding teaching children with autism spectrum disorder (ASD). Methods: 832 primary teachers from different states of West Malaysia participated in a web-based survey that assessed self-reported competency, knowledge and implementation practices with regards to managing children with autism spectrum disorder. Results: Respondents rated themselves as quite competent, and believed that they were knowledgeable regarding ASD and could implement ASD tasks. Frequency of training was a consistent predictor of competency. Respondents who had never attended a training course had significantly lower self-competency, lower level of knowledge, and lower implementation ratings than those who had attended even one course. Conclusions: Investments in training teachers on ASD are highly recommended to ensure these students are provided with quality of education they deserve.